IMPLEMENTASI PROBLEM BASED LEARNING TERHADAP KEMAMPUAN SISWA DALAM MENYELESAIKAN MASALAH MATEMATIS DITINJAU DARI GENDER SISWA SD NEGERI 21 PALEMBANG - Ahmad Tolib Amrullah; Nila Kesumawati; Nugroho Notosutanto Arhon Dhony (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted to determine whether or not there is an influence of the Problem Based Learning model on the ability to solve mathematical problems based on the gender of students of State Elementary School 21 Palembang. This study is included in the type of quantitative research with an experimental design. Data collection techniques using tests. Data analysis of this study used two-way anova. This study was conducted at State Elementary School 21 Palembang with a research sample of class V totaling 47 students/i divided into two classes, namely class Va experiment with 25 students and class Vb control with 22 students. From the data analysis, it can be concluded that There is a Significant Influence of the Problem Based Learning Model on Mathematical Problem Solving Ability obtained from H_oditolak and H_a accepted with a Sig value = 0.0009 <0.05. There is also no significant difference in the average mathematical problem solving ability based on gender with a sig value = 0.183 > 0.05. And there is no significant interaction between the learning model and gender on mathematical problem solving ability obtained a sig value = 0.307 > 0.05.